2008
DOI: 10.2522/ptj.20070205
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the Berg Balance Scale in Stroke Rehabilitation: A Systematic Review

Abstract: The BBS is a psychometrically sound measure of balance impairment for use in poststroke assessment. Given the floor and ceiling effects, clinicians may want to use the BBS in conjunction with other balance measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
626
2
31

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 955 publications
(710 citation statements)
references
References 33 publications
12
626
2
31
Order By: Relevance
“…In addition, the tendency for low or high scores shown by the sign of the correlation was consistent with previous research [26,27]. The limited correlation values (overall in the directional control measures), motivated by the different nature of the tests, indicated that the WBB-based posturography assessment can provide additional data not reflected in clinical tests and scales, thus supporting its use for complementing the balance assessment in individuals with stroke [28].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, the tendency for low or high scores shown by the sign of the correlation was consistent with previous research [26,27]. The limited correlation values (overall in the directional control measures), motivated by the different nature of the tests, indicated that the WBB-based posturography assessment can provide additional data not reflected in clinical tests and scales, thus supporting its use for complementing the balance assessment in individuals with stroke [28].…”
Section: Discussionsupporting
confidence: 87%
“…Moderate correlations have been reported not only between posturography and clinical tests [26], but also among clinical scales [27]. Previous correlations of COP measures using the WBB and clinical scale have been shown to support our results [11].…”
Section: Discussionsupporting
confidence: 87%
“…The maximum score indicates good balance, and a score below 45 indicates increased fall risk in the elderly population. 24 The BBS is a reliable and valid measure of functional balance in the stroke population, 25 with excellent inter-rater reliability (intraclass correlation coefficient (ICC)=0.98). 23 The Chedoke-McMaster Stroke Assessment (CMSA) 26 leg and foot sub-scales of the impairment inventory were used to determine participants' motor recovery.…”
Section: Data Collectionmentioning
confidence: 99%
“…However, common clinical balance measures such as the Functional Reach Test and Single Leg Stance, are single‐task measurements which could not assess multiple domains of balance and thus have limited value in directing treatment. The Berg Balance Scale (BBS) is a multi‐item generic balance measure, but its ceiling effects have been well documented when administered to individuals even as early as three months post‐stroke (Blum & Korner‐Bitensky, 2008; Mao, Hsueh, Tang, Sheu, & Hsieh, 2002). Postural Assessment Scale for Stroke Patients (PASS) is a stroke‐specific, multi‐item clinical assessment of balance (Benaim, Perennou, Villy, Rousseaux, & Pelissier, 1999).…”
Section: Introductionmentioning
confidence: 99%